Pungut Ulang Perak dari Limbah Elektronik Baterai Koin Perak Oksida Menggunakan Pelarut Deep Eutectic Oksalin - Fatimah, Soja Siti; Nugraha, Agung Slamet; Mora, Abraham (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2022)
Silver is a metal that has the highest electrical conductivity, thermal conductivity and reflectivity among all metals and by 2021 the world's silver demand will reach 32,627 tons. To meet the world's silver demand, apart from mining from nature, silver can also be obtained through re-collection of electronic waste using environmentally friendly Deep Eutectic Solvent (DES). The aim of this study was to recover metallic silver from electronic waste of silver oxide coin batteries using oxalin DES leaching method. The research methodology consisted of the steps of synthesizing the eutectic solvent oxalin, characterizing it, and its application to the leaching of silver from the cathode of a silver oxide battery. Silver leaching was carried out by dissolving 0.2 grams of sample with 1:1 oxaline solvent by direct heating for 3 × 8 hours at 500 rpm. The leaching temperature variations were 50, 60, 70, and 80oC and the volume variations of the DES oxalin used were 20, 40, 60, 80, 100, and 125 mL/g. The concentration of leached silver was measured using AAS instrumentation. The results of the synthesis were characterized by FTIR indicating the formation of a new intermolecular interaction, namely the COOH••••Cl interaction. DES oxalin has a density of about 1.2095 g/mL. Based on the results of the optimization of the leaching temperature using 20 mL/g of solvent, the optimum temperature for leaching was found at 60oC with a leaching efficiency of 88.35%. While the results of the volume optimization of the solvent carried out at the optimum temperature, it was found that the optimum volume of the solvent used was 80 mL/g of sample with a leaching efficiency of 94.23%. Based on these results, it can be seen that oxaline has the potential to be used as a solvent in the treatment of used silver oxide battery waste.